2019
DOI: 10.9734/ajaar/2019/v10i430034
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Biostimulants in High-density Olive Growing: Quality and Production

Abstract: Due to the increase of high-density holdings, especially of olive trees, the nutritional requirements of the plants are higher per unit area, which implies that a greater contribution of fertilizers to the soil is needed. Opting for fertilizers of inorganic origin will produce an increase in the pollution of the soil. In the face of this possible soil contamination, our aim is to analyze the effect of biostimulants as an alternative to chemical fertilizers, to steadily produce and maintain high quality standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Adaptation from [22] The values found in fruit weight and pulp-pit ratio are similar to those reported by previous research in 'Manzanilla' under similar agro environmental conditions [33]. The little or no response of the application of biostimulants to improve olive fruit quality is in accordance with that reported by [17,18] using different types of biostimulant on different olive tree varieties. Olive fruit size and pulp-pit ratio are important characteristics for table olive production.…”
Section: Fruit Characteristicssupporting
confidence: 86%
See 1 more Smart Citation
“…Adaptation from [22] The values found in fruit weight and pulp-pit ratio are similar to those reported by previous research in 'Manzanilla' under similar agro environmental conditions [33]. The little or no response of the application of biostimulants to improve olive fruit quality is in accordance with that reported by [17,18] using different types of biostimulant on different olive tree varieties. Olive fruit size and pulp-pit ratio are important characteristics for table olive production.…”
Section: Fruit Characteristicssupporting
confidence: 86%
“…Actually modern fruit trees physiology is focused on the stimulation of plant cell development and fruit production using bioestimulant. Foliar and soil applications with different types of biostimulants during flowering and fruit set in olive trees have increased fruit set, productivity and fruit quality [14,15,16,17], increase in oil content and quality [15,16], also improved fruit quality by advancing and uniforming fruit ripening [15,18].…”
Section: Introductionmentioning
confidence: 99%
“…Investigations with olive trees sprayed with humic acid at the beginning of the fruit set, led to a higher yield, fruit size and weight, and pulp/pit ratio (Haggag et al 2013). An improvement in the set of physical characteristics of the olives after the application of amino acids and extra K has been also observed (Hernández-Hernandez et al 2019). Other studies have shown the potential of an extract obtained from the aquatic duckweed (Lemna minor L.), with a high content of phenolic acids, phenols and flavonoids, to act as a biostimulant in olives, improving the leaf photosynthetic activity and chlorophyll content, plant growth and nutritional status (Regni et al 2021).…”
mentioning
confidence: 87%
“…For the Alcygol biostimulant, an increase of carotenoids and a reduction of peroxide value and total phenols was observed, while with the use of Nectar intense, the monounsaturated fatty acids (MUFAs) and carotenoids increased but the polyunsaturated fatty acids (PUFAs) decreased. Hernández-Hernandez et al [140] showed that the application of biostimulants based on algae and amino acids supplemented with nutrients on olive plants from the cvs 'Chemlali' and 'Arbequina' (in high density orchards) improved fruit weight but not alter oil quality (e.g., fatty acids, polyphenols and tocopherols). In olive orchards, the application of A. nodosum reduced olive oil acidity (%) but improved to levels of total phenols [4].…”
Section: Biostimulant Effect On Olive Fruits Oil Yield and Qualitymentioning
confidence: 99%